The Influence of Country of Origin (COO) on Indonesian Coffee Consumers Purchase Decision - Safira, Rahma Syifa; Aprilianty, Fitri (Journal of Business and Management, 2019)
The world coffee consumption is experiencing a positive growth that has recorded to increase at an average annual growth rate of 1.9%. Indonesian coffee consumption has been significantly increasing every year starting from 2010 until 2018. Indonesian’s desire for coffee along with coffee products continues to grow. From the country-of-origin (COO) point of view, COO has a contribution towards consumer’s evaluation of a product. COO effect does not only depend on the effective perceived quality image of the country, but also on consumers’ feelings toward it. This research focuses on consumer purchase decision by examining cognitive, affective and normative mechanisms in consumer preference formation for domestic vs imported coffee products. Data is drawn from a survey of 224 coffee consumers who were ascertained to regularly drink coffee. The research instrument and its measurements were adapted from previous studies. The measurement model was tested via PLS SEM method which was processed using SmartPLS 3.0 software. Once the construct reliability and validities were established, the structural model was evaluated to test the relationship among the hypotheses. The findings suggest that COO affects purchase behaviour of coffee products by Indonesian consumers where cognitive and normative mechanism are stronger determinants of domestic consumption than affective mechanism. Furthermore, Indonesian coffee products are supported by several parties so the business is growing, and Indonesian coffee products are expected to face opportunities and challenges in the future. The findings of this paper will also indicate the importance for the businesses in coffee industry to have knowledge and fully prepared with the prospects and challenges that they might be facing prior to developing their businesses. The implication of this research is that the education about coffee among coffee farmers needs to be boosted in order to produce better coffee quality, also business should emphasize more about the Indonesian-made originality along with the quality of Indonesian coffee marketing communication to develop personal bonds with the consumers which will help the brands to keep retained in consumers’ minds.Keywords: Affective, cognitive, COO, Indonesian coffee, normative, purchase decision